DETERMINANTS OF ANXIETY LEVELS IN PULMONARY TB PATIENTS DURING THE COVID 19 PANDEMIC - Pariyana Pariyana; Dewi Anggraini; Hanna Marsinta Uli; Chris Alberto Amin; Toto Harto (Majalah Kedokteran Sriwijaya, 2022)
Pulmonary tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis which is currently a major global health problem. While our world still in COVID-19 pandemic situation. Anxiety is a natural human behaviour that manifests itself as a bodily response to dangers.Mycobacterium tuberculosis infection as a more common comorbidity for COVID-19 by 36% and from the situation of the spread of COVID-19 which has almost reached all provinces in Indonesia with the number of cases and the number of deaths increasing, researchers are interested in conducting research on the determinants of the level of Anxiety of pulmonary TB patients in the COVID-19 pandemic situation in Palembang City. Using the Hamilton Rating Scale for Anxiety (HARS) as instrument we collect data regarding anxiety level among pulmonary tuberculosis patients in COVID-19 pandemic settings. Researchers discovered that responders were 131 pulmonary tuberculosis patients who were recruited from public health centers in Palembang City, based on researcher observations and questionnaires. Overall, there are significant relation regarding anxiety levels and its determinant factor on tuberculosis patient, especially in COVID-19 pandemic settings.